Applying a copula to the estimation of value-at-risk - Ang, Fang Ting (2013)
Value-at-Risk (VaR) is a common tool employed in the estimation of market risk. Traditionally, VaR of a portfolio is estimated through an assumption of normally distributed portfolio returns. Yet, as we delve further into the estimation of VaR, we believe that returns are not always normally distributed, and there are lapses in this assumption resulting in the underestimation of VaR.